PENGARUH MODIDFIKASI BOLA PLASTIK TERHADAP PENINGKATAN PASSING BAWAH BOLA VOLI PADA SISWA EKSTRAKURIKULER SMP NEGERI SATU ATAP 1 KABUPATEN KARAWANGAN - Khoer Ibnu Parta; Dhika Bayu Mahardika; Abdul Salam Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low underhand passing skills of junior high school extracurricular students due to limited training media and fear of using standard balls. The purpose of this study was to determine the effect of plastic ball modification on improving the underhand passing skills of junior high school extracurricular students at SMP Negeri Satu Atap 1 Kabupaten Karawang. The research employed an experimental method with a quantitative approach and a one-group pretest–posttest design. The research subjects consisted of 27 volleyball extracurricular students. Data collection techniques were conducted through underhand passing skill tests before and after the intervention, while data analysis used descriptive statistical tests and paired difference tests. The results showed an increase in the average underhand passing ability of students after being given treatment in the form of training using modified plastic balls. These findings indicate that plastic ball modification is effective in improving underhand passing skills because it provides a sense of safety, increases the frequency of training, and encourages active student participation. The study concluded that the use of plastic balls as a modified training medium positively influenced the improvement of students' underhand passing skills in volleyball. The implication of this research is that teachers and coaches are advised to utilise plastic balls as an alternative medium for teaching and practising basic volleyball techniques in schools.